Correction of pelvic organ prolapse by laparoscopic lateral suspension with mesh: A clinical series. (September 2019) - Martinello, Ruby; Scutiero, Gennaro; Stuto, Angelo; Indraccolo, Ugo; Cracco, Francesco; Borghi, Chiara; Sorrentino, Felice; Nappi, Luigi; Greco, Pantaleo
Abstract: Objective: Illustrating the outcomes of laparoscopic lateral suspension by mesh for pelvic organ prolapse repair. Study design: A retrospective observational study was conducted collecting medical records of 48 patients treated between May 2016 and April 2018 in two different centers in Italy. Pre- and post-operative clinical evaluations as well as patients' satisfaction scores were considered. Patients were followed for two years. Statistical analysis was determined using the chi-square test in intention-to-treat and per-protocol analyses, while Kaplan-Meier curves were built for assessing the prolapse recurrence and the symptoms recurrence. The Steel-Dwass test for pairwise comparisons was used to compare median scores from the King's General Health Perception Questionnaire answers. Results: Regarding the anatomical result, the outcome was either optimal or satisfactory (PoP-Q ≤1) at 12 months in 92% of patients for anterior compartment, in 100% for apical compartment, and in 75% for posterior compartment (intention-to-treat). Kaplan-Meier curves depicted a repair of prolapse in 70% of cases, with better outcomes for the anterior and the apical compartment. Patient self-perception of health was over 80% at each follow-up evaluation. Conclusion: Laparoscopic lateral suspension is a reasonable technique for treatment of pelvic organ prolapse. Further studies are needed to prove such a technique versus alternative surgeries.